Organ Donation Process for Transplantation: A Scoping Review - Silva, Tatiane Ribeiro da; Ronaldo Rocha Bastos; Emidio, Suellen Cristina D; Carbogim, Fabio da Costa; Braz, Patrícia Rodrigues (Brazilian Journal of Transplantation, 2024)
Objectives: To identify studies in the literature that address the strategies used in the organ donation process. Method: Scoping review based on the Joanna Briggs Institute ( JBI) methodology, in the databases Medical Literature and Retrieval System Online (MEDLINE), Scopus, Web of Science, Latin American and Caribbean Literature in Health Sciences (LILACS), and Embase via the Virtual Health Library (VHL), following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) checklist, carried out from August to December 2023. Results: Thirty-three studies were eligible, which showed that the donation process must happen systematically, following the steps: 1) identification of patients suspected of having brain death (BD); 2) opening the protocol and notifying organizations; 3) confirmation of the diagnosis of BD; 4) communicating the death to the family; 5) conducting the interview; 6) consent to donation; 7) donor maintenance; 8) procurement and allocation of organs; 9) transplant; and 10) follow-up. Conclusion: Donation requires a multifaceted approach, including awareness, investment, evaluation and research.